Bottlebrush polymers: From controlled synthesis, self-assembly, properties to applications - Li, Zili; Tang, Miao; Liang, Shuang; Zhang, Mingyue; Biesold, Gill M.; He, Yanjie; Hao, Shu-Meng; Choi, Woosung; Liu, Yijiang; Peng, Juan; Lin, Zhiqun (Progress in polymer science, 2021)
Bottlebrush polymers (BBPs) have emerged as intriguing class of materials for an array of applications, including supersoft elastomers, organic optoelectronics, templates for crafting one-dimensional (1D) nanomaterials, energy storage, and biomedical devices. The densely-grafted side chains along the linear backbones afford BBPs with extended cylindrical shapes and the absence of entanglements. The architectures of BBPs can be readily tuned by manipulating the chemical structures and compositions, both of which govern the viscoelastic properties, melt processability, and alignment of BBPs. This enables the crafting of BBPs with controlled dimensions, compositions, and architectures by capitalizing on advanced synthetic techniques. However, challenges remain in the synthesis and applications of BBPs with precisely controlled architectures. This review aims to provide a comprehensive and critical summary that highlights the recent advances in BBPs in terms of their controlled syntheses, self-assembly, properties, and applications. In addition, challenges facing the syntheses and applications of BBPs will be underscored, with the corresponding solutions to these issues for improving the control over chemical structures (e.g., introducing conjugated side chains), compositions (e.g., other than the widely used polynorbornene or polyacrylate backbone), and utilities (e.g., as solid-state electrolyte in energy storage devices) of BBPs. [Display omitted]